Numerical simulation of aircraft crash on large-scale LNG storage tank. (February 2019) - Peng, Q.; Wu, H.; Wang, D.W.; He, Y.J.; Chen, H.
Abstract: The safety of the large-scale LNG (liquid natural gas) storage tank is threatened by the accidental or deliberate aircraft collisions, while the related studies are limited. At present, based on the missile-target interaction method, the dynamic damage and failure of the Chinese Yang Shan pre-stressed LNG storage tank against the impact of the commercial aircraft A320 are assessed numerically. Firstly, the fine FE (finite element) models of LNG storage tank and Airbus A320 aircraft are established with the program HyperMesh, which are validated by comparing with the classic IRIS (Improving the Robustness of Assessment Methodologies for Structures Impacted by Missiles) impact test of deformable missile as well as the modified Riera function, respectively. Then, the whole impact process of A320 aircraft on the LNG storage tank is reproduced with the explicit dynamic analysis program LS-DYNA. The impact force-time history, the deflection of the outer concrete tank, the effective plastic strain of the inner steel tank, et al. are obtained and discussed. Finally, the parametric analyses are performed to study the influences of the impact velocity, angle and position on the dynamic responses of the LNG storage tank. The conclusions are helpful for the design and safety assessment of LNG storage tank subjected to the potential aircraft collision. Highlights: Fine FE models of Chinese Yang Shan LNG pre-stressed storage tank and A320 aircraft are established and validated. The dynamic damage and failure of LNG storage tank subjected to commercial aircraft impact are numerically assessed. Influences of the impact velocity, angle and position on the dynamic responses of LNG storage tank are further discussed.